2020
DOI: 10.1007/s13311-019-00816-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain–Machine Interface Induced Morpho-Functional Remodeling of the Neural Motor System in Severe Chronic Stroke

Abstract: Brain-machine interfaces (BMI) permit bypass motor system disruption by coupling contingent neuroelectric signals related to motor activity with prosthetic devices that enhance afferent and proprioceptive feedback to the somatosensory cortex. In this study, we investigated neural plasticity in the motor network of severely impaired chronic stroke patients after an EEG-BMIbased treatment reinforcing sensorimotor contingency of ipsilesional motor commands. Our structural connectivity analysis revealed decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 115 publications
1
10
0
3
Order By: Relevance
“…e EMG can be used to detect and evaluate the synergistic movements and spasticity of the upper limb after stroke. ere are many clinical treatments for my spasm, but they are not effective enough, so it is important to promote the reduction of hemiplegic limb spasticity in stroke patients as soon as possible [8]. e use of biosynthetic testing connected with surface EMG makes it possible to test more precisely, while the muscle is contracting, to observe the muscle firing capacity, and thus to assess muscle function more scientifically.…”
Section: Introductionmentioning
confidence: 99%
“…e EMG can be used to detect and evaluate the synergistic movements and spasticity of the upper limb after stroke. ere are many clinical treatments for my spasm, but they are not effective enough, so it is important to promote the reduction of hemiplegic limb spasticity in stroke patients as soon as possible [8]. e use of biosynthetic testing connected with surface EMG makes it possible to test more precisely, while the muscle is contracting, to observe the muscle firing capacity, and thus to assess muscle function more scientifically.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Ramos-Murguialday et al, 2013, demonstrated that after ipsilesional BMI training, bihemispheric changes in function and structure occur in chronic stroke patients 5,49 . Therefore, the bihemispheric interplay and its involvement in recovery is clear.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the above theory, we asked the following questions: 1) Could brain responses to subliminal emotional stimuli be modulated by the self-control of the posterior-frontal brain activity, and 2) would such a voluntary or self-regulated modulation in uence the threshold for conscious perception? To answer these questions we developed an rtfMRI neurofeedback system (Caria et al, 2020;Sitaram et al, 2017;Birbaumer et al, 2013;Sulzer et al, 2013;Rana et al, 2013) for instrumental conditioning of BOLD activity in the four regions of interest (ROIs), namely, the right primary visual cortex (PVC; involved in processing of shape, color and other basic attributes of visual stimuli) (Murray et al, 2006;Parkes et al, 2009; Kok and de Lange, 2014), right fusiform face area (FFA; specialized in processing facial stimuli) (Sergent et al, 1992;Kanwisher et al, 1999;Said et al, 2011), left anterior insula (INS; implicated in emotion processing) (Davidson and Irwin, 1999;Zaki et al, 2012) and bilateral anterior medial prefrontal cortex (AMPFC; part of the hypothesized global workspace to sustain the recurrent activation) (Dehaene et al, 2001;Del Cul et al, 2006;Del Cul et al, 2009). Such self-regulation of the BOLD response could be categorized in 2 types: self-controlled BOLD increase (up-regulation) and self-controlled BOLD decrease (down-regulation).…”
Section: Introductionmentioning
confidence: 99%